KEKUATAN YURIDIS FAKTA PERSIDANGAN DALAMPENGAMBILAN PUTUSAN OLEH HAKIM (STUDI KASUS PERKARA PIDANA NOMOR 1532/PID.B/2009/PN.JKT.SEL ATAS NAMATERDAKWAANTASARI AZHAR) - Denu Pahlawardi; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The factthe trialisthe factthatemerges fromthe evidence andthe evidenceshownat trial. Considerationdroppingadecisionmust bebased onthe factthatthe trialis constructedintoaseries offact that there wasacriminal offense. Legally, the factsarebasicconsiderationsforthe trialjudgein making the decision. theSouthJakarta District Courton behalf ofdefendantNo.1532/Pid.B/2009/PN.Jkt.SelAzhar, thatthe judgesdo notemploy the use ofthe factsthatemergedfromthe trialevidenceandlegalevidenceandfiledin the trialas the basisconsiderationbydeciding the case.Key words: Kekuatan Yuridis –FaktaPersidangan – Putusan Hakim